Pengaruh Surat Berharga Syariah Negara Dan Penyaluran Pembiayaan Terhadap Profitabilitas Bank - Muna Aulia Rahma; Djoni Djatnika; Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to analyze the effect of investment ownership of Sovereign Sukuk (SBSN) and Financing Distribution on profitability which is proxied by Net Income Margin (NIM) at Bank Syariah Mandiri in the 2013-2020 periode. This research is associative because it aims to determine the influence and relations between two variables. The data used in this study are secondary data obtained from the quarterly financial reports of Bank Syariah Mandiri in the periode 2013-2020, data obtained from the Otoritas Jasa Keuangan (OJK) and other data related to the subject and object of research. This study uses multiple linear regression analysis method and the analytical tool used is SPSS version 25. The results show that simultaneously the variables of Sovereign Sukuk and Financing do not have a significant effect on Net Income Margin. Partially the SBSN variable does not have a significant effect on the NIM variable, as well as the Financing variable does not have a significant effect on the NIM variable.